172 CLINICAL AND PROGNOSTIC IMPLICATIONS OF RV UPTAKE WITH RADIONUCLIDE SCINTIGRAPHY IN TRANSTHYRETIN CARDIAC AMYLOIDOSIS. (15th December 2022) - Porcari, Aldostefano; Fontana, Marianna; Canepa, Marco; Biagini, Elena; Cappelli, Francesco; Gagliardi, Christian; Longhi, Simone; Pagura, Linda; Tini, Giacomo; Dore, Franca; Bonfiglioli, Rachele; Bauckneht, Matteo; et al.
Abstract: Aims: The prognostic role of bone tracer uptake in transthyretin cardiac amyloidosis (ATTR-CA) is controversial. The study investigated the potential prognostic significance of biventricular (BiV) uptake in ATTR-CA. Methods: Consecutive ATTR-CA patients who had cardiac scintigraphy with acquisition of planar and single-photon emission computed tomography (SPECT) images from the National Amyloidosis Centre (NAC) and four Italian centres were included. Planar BiV uptake was defined in presence of right ventricle (RV) uptake and graded in combination with SPECT imaging. The primary outcome was all-cause mortality. Results: Among 1422 patients with ATTR-CA, BiV uptake was found in 85% of cases on planar scintigraphy and in 100% of cases on SPECT images. During a median follow-up of 39 months, BiV uptake at planar scintigraphy was associated with a higher all-cause mortality compared to isolated LV uptake (40.5% vs 10.7%, p<0.001), whereas the Perugini scale was not (p=0.27 in grade 2 vs 3). At multivariable analysis, RV uptake at planar scintigraphy leading to BiV uptake (HR 2.80, p=0.001), together with higher age at diagnosis (HR 1.03, p=0.001), V122I TTR variant (HR 1.60, p=0.001), NAC ATTR Stage (HR 1.29, p=0.003), E/e' (HR 1.02, p=0.044), right atrium area index (HR 1.04, p=0.018) and GLS (HR 1.05, p=0.003) were independently associated with all-cause death. At time-dependent ROC curve analysis, the addition of planar BiV uptake to the NAC stage resulted in improved accuracy of the model for prediction of all-cause death (from AUC 0.74 to 0.79; p<0.001). Conclusions: Planar RV uptake leading to BiV uptake identified ATTR-CA patients with worse outcome, potentially serving as a novel prognostic marker.